An in vitro visual study of fugitive aerosols released during aerosol therapy to an invasively ventilated simulated patient - Marc Mac Giolla Eain; Mary Joyce; Ronan MacLoughlin (Taylor & Francis Group, 2021)
COVID-19 can cause serious respiratory complications resulting in the need for invasive ventilatory support and concurrent aerosol therapy. Aerosol therapy is considered a high risk procedure for the transmission of patient derived infectious aerosol droplets. Critical-care workers are considered to be at a high risk of inhaling such infectious droplets. The objective of this work was to use noninvasive optical methods to visualize the potential release of aerosol droplets during aerosol therapy in a model of an invasively ventilated adult patient. The noninvasive Schlieren imaging technique was used to visualize the movement of air and aerosol. Three different aerosol delivery devices: (i) a pressurized metered dose inhaler (pMDI), (ii) a compressed air driven jet nebulizer (JN), and (iii) a vibrating mesh nebulizer (VMN), were used to deliver an aerosolized therapeutic at two different positions: (i) on the inspiratory limb at the wye and (ii) on the patient side of the wye, between the wye and endotracheal tube, to a simulated intubated adult patient. Irrespective of position, there was a significant release of air and aerosol from the ventilator circuit during aerosol delivery with the pMDI and the compressed air driven JN. There was no such release when aerosol therapy was delivered with a closed-circuit VMN. Selection of aerosol delivery device is a major determining factor in the release of infectious patient derived bioaerosol from an invasively mechanically ventilated patient receiving aerosol therapy.